Is meningococcal B vaccination needed in the post-COVID-19 world? - Izeli Portilho, Amanda; De Gaspari, Elizabeth (Biomedica : revista del Instituto Nacional de Salud, 2025)
Neisseria meningitidis is the main cause of bacterial meningitis worldwide and is transmitted through respiratory secretions. Meningitis is a serious public health problema because of its high morbidity and mortality rates and the risk of causing epidemics.Although vaccines are available to prevent meningococcal disease, serogroup B infections are still challenging, given that many countries do not include meningococcal B vaccines in their national immunization programs. In addition, recent data suggests somewhat sustained N. meningitidis B infections during the COVID-19 pandemic and increasing levels of meningococcal disease after its control. These findings agree with previous observations indicating that respiratory viruses facilitate respiratory bacterial infections.This essay intends to present epidemiological data on meningococcal disease and discusses studies exploring why the prevention of bacterial and viral infections is an intricate subject. Neisseria meningitidis es la principal causa de meningitis bacteriana en el mundo y es transmitida mediante secreciones respiratorias. La meningitis es un grave problema de salud pública debido a sus grandes tasas de morbilidad y mortalidad, y por el riesgo de generar epidemias.Aunque existen vacunas para prevenir la enfermedad meningocócica, la infección por el serogrupo B sigue siendo un desafío, ya que muchos países no han incluido estas vacunas en sus programas nacionales de inmunización. Además, datos recientes sugieren la persistencia de infecciones causadas por el serogrupo B de N. meningitidis durante la pandemia de COVID-19 y un incremento en los niveles de enfermedad meningocócica tras su contención. Esta información coincide con observaciones previas que afirman que los virus respiratorios facilitan las infecciones bacterianas respiratorias.Este ensayo pretende presentar datos epidemiológicos de la enfermedad meningocócica y discutir aquellos estudios que resaltan la complejidad de la prevención de las infecciones bacterianas y virales.